The exchange rate control - Hungarian experiences - Dorota Zbierzchowska (Ekonomia i Prawo, 2009)
Since the 1990s various kinds of exchange rate regimes have been employed, such as the adjustable peg regime, the crawling peg regime and the so-called ERM II shadow. This article aims at presenting Hungarian experiences concerning the exchange control policy and the effects of its application. Many negative consequences of employing and using a fixed exchange rate arrangement emerged, mostly those related to the limitation of the autonomy of monetary policy and to the danger of speculation in the foreign exchange market, which in 2008 led to abandonment of the forint’s trading band and introduction of the free-float exchange rate regime.